An Overview of the Quality of Life of Post Severe Brain Injury Patients within 2018-2020 Period of Time in Dr. Soetomo General Academic Hospital based on Short Form-36 - Agus Turchan; Alivery Raihanada Armando; Meisy Andriana; Martha Kurnia Kusumawardani (Universitas Airlangga, 2022)
Highlight: Until today, Traumatic Brain Injury is still a major cause of death, disability, and a serious health issue Traumatic Brain Injury patients have a good quality of life if they get adequate therapy and on time interventions ABSTRACT Introduction: Approximately 90 million traumatic brain injury (TBI) cases worldwide exist yearly. TBI pathophysiology varies, which may cause diverse complications. These complications may decrease the patients’ quality of life. Objective: Describing the quality of life of traumatic brain-injured patients after being treated at Dr. Soetomo General Academic Hospital Period 2018-2020. Methods: This research is a descriptive cross-sectional study using SF-36 questionnaire data from patients with post-severe brain injury at Dr. Soetomo General Academic Hospital in 2018-2020. Results: The value of the physical component (59.9) and mental component (68.6) in patients with severe brain injury at Dr. Soetomo General Academic Hospital showed a good quality of life, with values ​​in the SF-36 domains, namely physical function (58.2), physical limitations (46.7), body pain (73.6), general health (61.3), vitality (65.3), social functioning (72.5), emotional limitations (60), and mental health (76.5) is above the threshold value (50) except for physical limitations (46.7).Conclusion: Patients with severe brain injury had a good quality of life after receiving treatment in Dr. Soetomo General Academic Hospital.